Comorbidities and co-infections in people living with HIV/AIDS - Rosângela Casas Righetto; Renata Karina Reis; Lílian Andreia Fleck Reinato; Elucir Gir (Rev Rene, 2015)
It is a cross-sectional study made in three clinics specialized in the care of infectious diseases in Ribeirão Preto, SP, Brazil, in order to identify the prevalence of co-infections and comorbidities in people living with HIV / AIDS. Demographic and clinical variables were analyzed from 498 medical records of patients from December, 2004 to June, 2010. Data analyzed using descriptive statistics show an average of 39.3 years of age, ranging from 17 to 71 years, with 295 (59.2%) males. 390 comorbidities were observed (78.3%), especially dyslipidemia 126 (25.3%), triglycerides 68 (13.7%), hepatitis C 68 (13.7%), oral candidiasis 60 (12.0 %), sexually transmitted disease 57 (11.4%) and tuberculosis 51 (10.2%). Depending on the different comorbidities, it is considered appropriate that special strategies to monitor are planned, for the diagnosis and early intervention.